1980
DOI: 10.1002/1097-0142(19800901)46:5<1187::aid-cncr2820460518>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal seminomas

Abstract: A series of malignant seminomas of the mediastinum is presented and compared with previously reported series. The difficulty of conclusively excluding occult primary gonadal disease is noted. Primary mediastinal seminomas are associated with a better prognosis than teratomas of this site, mainly because of their radiosensitivity. A case report of a patient with mediastinal seminoma and two congenital abnormalities (ventricular septal defect and congenital absence of a thoracic hemivertebra) is presented and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

1985
1985
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…After teratoma, seminoma is the second most common germ cell tumor of the mediastinum in its pure form 19, 20. However, the true incidence of seminomas has been difficult to assess due to the relatively small series of cases reported until now 21‐46. In our experience, primary mediastinal seminomas have accounted for approximately 37% of all mediastinal germ cell tumors and taken second place only to teratomas.…”
Section: Discussionmentioning
confidence: 76%
“…After teratoma, seminoma is the second most common germ cell tumor of the mediastinum in its pure form 19, 20. However, the true incidence of seminomas has been difficult to assess due to the relatively small series of cases reported until now 21‐46. In our experience, primary mediastinal seminomas have accounted for approximately 37% of all mediastinal germ cell tumors and taken second place only to teratomas.…”
Section: Discussionmentioning
confidence: 76%
“…Nonetheless, such tumors have also been described in other locations, such as the pineal gland, retroperitoneum, mediastinum, and sacral area 2‐4. Germ cell tumors arising primarily in the mediastinum are uncommon and have mostly been the subject of case reports; very few comprehensive studies on this topic have been reported in the literature 2, 4‐103. It has been estimated in some studies that extragonadal germ cell tumors account for approximately 1‐15% of mediastinal tumors in adults and approximately 25% in children 21, 59, 60, 104…”
mentioning
confidence: 99%
“…O seminoma de mediastino apresenta melhor prognóstico que tumores mediastinais não-seminoma, e pior em relação aos seminomas gonadais, 25 pois: no testículo, a túnica albugínea envolve o tumor e evita disseminação precoce; no mediastino, o tumor geralmente se apresenta em estadio mais avançado, por apresentar poucos sintomas, mesmo quando relativamente grandes; e haver a tendência à disseminação hematogênica, tendo em vista sua localização.…”
Section: Discussionunclassified